Association between types of diets and clinical outcome in critically ill patients malnourished (Research, Society and Development, 2023)
Malnutrition is recurrent in hospitalized patients and the diet received during the hospitalization period can trigger positive clinical effects. In this perspective, this work aims to correlate the types of diets offered with the clinical outcome of patients who presented hospital malnutrition. It is a longitudinal descriptive study, carried out based on data (gender, age, body mass index, diet therapy and clinical outcome) collected from the medical records and records of 59 malnourished patients at the Maria Aparecida Pedrossian University Hospital in Campo Grande/MS, in the interval from March to September 2022. The results found showed that 62.71% (n=37) of the patients were elderly (60 to 90 years old) and 37.29% (n=22) were adults (18 to 59 years old). In addition, there was a prevalence of males represented by 72.89% (n=43) to the detriment of females with 27.11% (n=16). Regarding diet therapy, enteral HPHC diet (1.5 kcal/ml) and oral diet, with a sum of 38.97% (n=22), had greater associations with hospital discharges. However, regarding the clinical outcome, there was a predominance of deaths, with a percentage of 49.15% (n=29) among malnourished patients, followed by hospital discharges with 44.07% (n=26) and hospital transfers indicating 6.78% (n=4). In conclusion, this work made it possible to identify the nutritional behaviors that had the most impact on clinical outcomes and highlight the importance of Nutritional Therapy in malnourished critically ill patients.